2003
DOI: 10.1051/0004-6361:20030711
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the COROT space mission: Incidence and characterisation of pulsation in the lower instability strip

Abstract: Abstract. By pursuing the goal to find new variables in the COROT field-of-view we characterised a sample of stars located in the lower part of the instability strip. Our sample is composed of stars belonging to the disk population in the solar neighbourhood. We found that 23% of the stars display multiperiodic light variability up to a few mmag in amplitude, i.e., easily detectable on a single night of photometry. uvbyβ photometry fixed most of the variables in the middle of the instability strip and high-res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The δ Sct variability of HD 174966 was discovered in the preparatory work of the CoRoT mission (Poretti et al 2003). HD 174966 was observed in the same CoRoT frame as the other δ Sct-type star HD 174936 (GH09), during the first short run SRc01, between April 2007 and May 2007.…”
Section: Analysis Of the Light Curve Observed By Corotmentioning
confidence: 83%
“…The δ Sct variability of HD 174966 was discovered in the preparatory work of the CoRoT mission (Poretti et al 2003). HD 174966 was observed in the same CoRoT frame as the other δ Sct-type star HD 174936 (GH09), during the first short run SRc01, between April 2007 and May 2007.…”
Section: Analysis Of the Light Curve Observed By Corotmentioning
confidence: 83%
“…They also estimated the age to be about 1.8 ± 0.2 Gyr. Poretti et al (2003) have measured v sin i 23 km s −1 . They also found that HD 175272 does not show any evident trace of variability.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of pulsating stars compared to the total number of stars inside the instability strip is known as the incidence. The incidence of δ Sct in the MW, from the study of the Solar neighborhood and open clusters is somewhere between a quarter and half of the stars within the instability strip (Breger 2000;Poretti et al 2003;Balona & Dziembowski 2011), although the majority of these have very small amplitudes of a few milimagnitudes.…”
Section: Delta Scuti Starsmentioning
confidence: 99%